Lymph node metastases and recurrence in pancreatic neuroendocrine neoplasms - Nießen, Anna; Schimmack, Simon; Lewosinska, Magdalena; Hinz, Ulf; Bechtiger, Fabiola A.; Hackert, Thilo; Büchler, Markus W.; Strobel, Oliver (Surgery, 2022)
Background - The impact of lymph node metastasis on survival in pancreatic neuroendocrine neoplasms as well as their best surgical treatment is controversial. We aimed to determine the frequency and prognostic impact of lymph node involvement in pancreatic neuroendocrine neoplasms. - Methods - Patients undergoing pancreatic resections for pancreatic neuroendocrine neoplasms between 2001 and 2019 were retrospectively analyzed based on a prospective database. Clinicopathological parameters and perioperative outcome were assessed. Overall and disease-free survival was analyzed. Subgroup analysis was performed for sporadic, nonfunctional pancreatic neuroendocrine neoplasms without distant metastases and ≥4 analyzed lymph nodes. - Results - Of 605 surgically resected pancreatic neuroendocrine neoplasms, 55% were G1, 36% were G2, and 9% were G3 differentiated. At the time of resection, 34% of patients had lymph node metastasis, and 16% had distant metastases. For subgroup analysis, 314 patients were analyzed. Lymph node metastases occurred in 36% of patients and were most frequent in G3 patients (67%). An increase in tumor size and advancement was associated with higher rates of lymph node metastasis, and disease-free survival was significantly impaired. Significant differences in disease-free survival were observed between 1 and 3 (5-year disease-free survival 52%) and ≥4 positive lymph nodes (5-year disease-free survival 28%), as well as when G3 tumors were excluded. In multivariable analysis, grading, tumor stage, and especially lymph node metastases as well as the proposed pN1 and pN2 categories were confirmed as independent predictors of recurrence. - Conclusion - The presence and extent of lymph node involvement has considerable prognostic impact in pancreatic neuroendocrine neoplasms. This study, for the first time, validated the proposed pN2 stage for well-differentiated pancreatic neuroendocrine neoplasms.
Gesehen am 27.03.2023